Bacterial Ecology and Antibacterial Resistance Patterns: A Cross-sectional Study in the Internal Medicine Unit of Centre Médico-Chirurgical des Armées de Bamako, Mali - Lassina Diallo; Abasse Sanogo; Ladji Mohamed Diaby; Hassane Diallo; Sah Dit Baba Coulibaly; Yacouba Cissoko; Issa Konaté; Sounkalo Dao (Asian Journal of Research in Infectious Diseases, 2026)
Background: Antibacterial resistance (ABR) is a major public health threat, particularly in low- and middle-income countries where hospital surveillance data remain limited. This study aimed to describe bacterial ecology, antimicrobial resistance patterns, and factors associated with multidrug-resistant bacteria (MDRB) in the Internal Medicine ward of Centre Médico-Chirurgical des Armées de Bamako, Mali. Aim: This study aimed to characterise bacterial ecology and antimicrobial resistance patterns in this department and to identify factors associated with multidrug resistance. Methods: We conducted a descriptive and analytical cross-sectional study from January 2023 to December 2024. Among 840 hospitalised patients, 102 cases with microbiologically confirmed bacterial infections were included. Bacterial identification and antimicrobial susceptibility testing were performed using standard microbiological techniques. Multidrug resistance was defined as resistance to at least one agent in three or more antimicrobial classes. Associations between MDRB and clinical factors were analysed using chi-square tests. Results: Urinary tract infections accounted for 78.4% of cases, followed by bloodstream infections (12.7%), purulent samples (6.9%), and stool cultures (2.0%). The mean age was 55.5 years, with patients ≥60 years representing 47.1%. Males predominated (72.5%; sex ratio 2.6). The most frequently isolated pathogens were Escherichia coli (52.9%), Klebsiella pneumoniae (13.7%), Staphylococcus aureus (6.9%), Acinetobacter baumannii (4.9%), and Enterococcus faecium (4.9%). High resistance rates were observed to ampicillin, amoxicillin–clavulanic acid, cotrimoxazole, fluoroquinolones, and third-generation cephalosporins. Imipenem, ertapenem, and amikacin showed the lowest resistance rates. Overall, 51.0% of isolates were multidrug resistant. MDRB were significantly associated with HIV infection (p < 0.001), prior antibiotic use (p < 0.001), prolonged hospitalisation (p = 0.004), but not with urinary catheterisation or venous catheter use. Conclusions: A high burden of multidrug-resistant bacteria was identified in the Internal Medicine ward of Centre Médico-Chirurgical des Armées. Strengthening antimicrobial stewardship, infection prevention and control, and routine AMR surveillance is urgently needed.